THE EFFECT OF GRAMMAR WHEEL AND MIND MAPPING ON THE STUDENTS’ WRITING OF NARRATIVE TEXT OF THE EIGHTH GRADE OF SMPN 10 MUARA TEWEH - Saputra, Boby; Usadiati, Wahyuningsih; Asi, Natalina (Journal Compound: Improving the Quality of English Education, 2019)
Junior high school students like those in the eighth grade of SMPN 10 Muara Teweh still have difficulty in writing narrative text. This is because they are still weak in terms of writing and channeling ideas to be poured in narrative texts. The purpose of the study is to know whether or not there is a significant difference of the use of grammar wheel and mind mapping in students' ability to write narrative text as the media. The method was an experimental method with design of One-Shot Case Study design; the independent variable was grammar wheel and mind mapping, and the students' writing narrative text as the dependent variable. The population and sample were taken from the eighth grade students of SMPN 10 Muara Teweh. The data were analysed using SPSS 16.0 for Windows program. The result shows that there was a significant difference of the use of grammar wheel and mind mapping as media and without them. The use of Grammar Wheel media affected more significant than that of Mind Mapping in the students’ writing ability in narrative text.